(untitled) (Bangladesh Journal of Animal Science, 2022)
This research aimed to evaluate the quality of vermicompost produced from cattle manure at different levels of moisture content. For this purpose, cattle manure containing different moisture content such as 60% moisture (T1), 70% moisture (T2) and 80% moisture (T3) treatments were adopted with 3 replications. A total of 9 vermicomposting pits were filled with 25 kg of cattle manure, each having the same amount of red worms. Parameters studied were dry matter (DM), crude fibre (CF), crude protein (CP), ether extract (EE), ash and pH. Results showed that 63% DM was increased in T2 and this value was significantly higher than T1 and T3 (p> 0.05). The rate of CF degradation was 46, 78 and 72% in T1, T2 and T3, respectively. The CF degradation was also significantly higher in T2 compared to the other two treatments (p> 0.05). In the case of CP, a slightly higher CP was found in T2 followed by T1 and a little bit lower in T3 after 60 days of vermicomposting period. The EE content was slightly higher in all 3 treatments after 60 days of vermicomposting, but this difference was not significantly different among the treatments. The ash content was slightly higher in all 3 treatments after 60 days of vermicomposting, but this difference was also not significantly varied. The pH was significantly differed with the 3 treatments after 60 days of vermicomposting. From the above results, it was revealed that T2 would be the suitable level of moisture for CF degradation and increased CP content in the final vermicompost. Therefore, it might be concluded that cattle manure containing 70% initial moisture would be a good option for vermicomposting. Bangladesh Journal of Animal Science. 2022. 51 (2): 40-46